The Influence of Coconut Water and Activated Charcoal in MS Medium on In Vitro Callus Regeneration of Dendrobium sp. Cultivar Bertha Chong Orchids - Dessi Novita Sari; Zairin Thomy; Yunita Yunita (Universitas Syiah Kuala, 2015)
Dendrobium is one of the most commercial orchids. In Vitro technique is one of solution to fulfill the market demand of Dendrobium. Organic matters, such as coconut water, and activated charcoal are often given to in vitro medium to regenerate orchids callus. The addition of activated charcoal is not only adsorbing toxic substances but also organic matters. The aimof this researchistofindthe best combination for callus regeneration medium. The research was conducted at the Biological Cell and Molecular Laboratory, Mathematics and Natural Science Faculty of Syiah Kuala University, Darussalam, Banda Aceh since March to November 2013. The method used is experimental with Completely Randomized Factorial Design with two factor; treatments of coconut water and activated charcoal. The result showed that the combinationof 150mL/Lcoconut waterand2,0g/Lactivated charcoal is the best resultbecauseit is the onlytreatment that have capability in producingplantletswithin60days.